THE ROLE OF PHRASEOLOGICAL UNITS IN THE IDEOLOGICAL AND THEMATIC CONTENT OF CHILDE HAROLD’S PILGRIMAGE (International Conference on Education, Psychology and Humanities, 2026)
This article extensively investigates the role and artistic functions of phraseological units in shaping the ideological and thematic content of George Gordon Byron's poem "Childe Harold's Pilgrimage". Within the scope of the research, the stylistic and semantic potential of phraseological units in illuminating the themes of freedom, homeland, despair, and human values is analyzed. It is proven through a linguopoetic approach that phraseologisms in Byron's lyrics manifest as units carrying an ideological burden.
Keywords: Byron, Childe Harold's Pilgrimage, phraseological units, ideological-thematic content, linguopoetics, Romanticism, stylistic function, semantic analysis.